Antibacterial Effects and Biocompatibility of Titania Nanotubes with Octenidine Dihydrochloride/Poly(lactic-co-glycolic acid). (19th May 2015) - Xu, Zhiqiang; Lai, Yingzhen; Wu, Dong; Huang, Wenxiu; Huang, Sijia; Zhou, Lin; Chen, Jiang
Abstract : Titanium (Ti) implants with long-term antibacterial ability and good biocompatibility are highly desirable materials that can be used to prevent implant-associated infections. In this study, titania nanotubes (TNTs) were synthesized on Ti surfaces through electrochemical anodization. Octenidine dihydrochloride (OCT)/poly(lactic-co-glycolic acid) (PLGA) was infiltrated into TNTs using a simple solvent-casting technique. OCT/PLGA-TNTs demonstrated sustained drug release and maintained the characteristic hollow structures of TNTs. TNTs (200 nm in diameter) alone exhibited slight antibacterial effect and good osteogenic activity but also evidently impaired adhesion and proliferation of bone marrow mesenchymal stem cells (BMSCs). OCT/PLGA-TNTs (100 nm in diameter) supported BMSC adhesion and proliferation and showed good osteogenesis-inducing ability. OCT/PLGA-TNTs also exhibited good long-term antibacterial ability within the observation period of 7 d. The synthesized drug carrier with relatively long-term antibacterial ability and enhanced excellent biocompatibility demonstrated significant potential in bone implant applications.